PECVD SixCy as Barrier Layer Against Aluminum in Solar Cells With poly-Si/SiOx Passivating Contacts - David Bäurle; Benjamin Gapp; Giso Hahn; Heiko Plagwitz; Barbara Terheiden (SiliconPV Conference Proceedings)
We investigate the barrier properties of phosphorus-doped Si-rich silicon carbide (SixCy) thin films deposited by PECVD against Al/Si alloying in the context of poly-Si/SiOx passivating contacts. The stability of the implied open circuit voltage (iVOC) after firing of single-sided, full area screen-printed Al-contacts increases with carbon content of the barrier layer and depends on the crystallization scheme applied to the samples. Crystallized SixCy layers with an atomic C concentration of about 20 at.% deposited on pre-crystallized poly-Si predominantly show no significant decrease in iVOC values for peak firing temperatures up to 725°C.